Il "plurale di magnitudo": Prima parte (Carte Romanze, 2021)
The author discusses a particular type of plural, which he defines “of magnitudo”: it is a form that does not indicate a plurality of designata, but is related to an idea of greatness or historical or social importance and to other related parameters, with reference to a single designatum. He offers three examples: le cucine, i giardini, le carceri.
Keywords: morphosemantics; Italian language; plural